2023
DOI: 10.1007/s10516-023-09669-z
|View full text |Cite
|
Sign up to set email alerts
|

The Citadel Itself: Defending Semantic Internalism

Elliot Murphy

Abstract: Semantic internalism is the view that linguistic meaning amounts to forms of conceptual instructions, and that the process of forming linguistic representations does not involve reference to extra-mental entities. Contemporary philosophy of language remains predominantly externalist in focus, having developed systems of extensional reference which depart from classical rationalist assumptions. I will defend semantic internalism using a broad range of case studies, accruing what I see at the most convincing arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Going beyond this, in Murphy (2021c) it was shown that what I called the "persistence conditions" for copredication (the conditions under which certain complex polysemous nominals can sustain coherent sense relations in a brief narrative which "takes away" certain senses until the object referred to is reduced in sense number) are also correlated significantly with semantic complexity, not sense frequency. This provides further evidence for the centrality not of prediction, but of semantics (see Murphy 2023bMurphy , 2024a.…”
Section: Much Ado About Nothing: the Absence Of Frequency Effects In ...mentioning
confidence: 74%
“…Going beyond this, in Murphy (2021c) it was shown that what I called the "persistence conditions" for copredication (the conditions under which certain complex polysemous nominals can sustain coherent sense relations in a brief narrative which "takes away" certain senses until the object referred to is reduced in sense number) are also correlated significantly with semantic complexity, not sense frequency. This provides further evidence for the centrality not of prediction, but of semantics (see Murphy 2023bMurphy , 2024a.…”
Section: Much Ado About Nothing: the Absence Of Frequency Effects In ...mentioning
confidence: 74%
“…The blanket states can be partitioned into sensory states and active states. External states affect internal states only through sensory states, while internal states affect external states only through active states (Murphy, 2023a ). The implicit circular causality is formally identical to the perception–action cycle (Fuster, 2004 ).…”
Section: Active Inference and The Free-energy Principlementioning
confidence: 99%
“…1 MERGE serves a similar role to an elementary function, as in the theory of computability (e.g., the zero function, the identity function), in that it is meant to be non-decomposable. Putting many subsidiary technical details aside, these sets are then ‘labeled’ and given a syntactic identity, or a ‘head’ (Frampton & Gutmann, 1999 ; Leivada et al, 2023 ; Murphy et al, 2022 , 2023 ; Murphy, 2015a , b , c , 2023a ; Woolnough et al, 2023 ), based on which element is most structurally prominent and easiest to search for (i.e., Z in the structure {Z, {X, Y}}). 2 Labeling takes place when conceptual systems access the structures generated by syntax.…”
Section: Computational Principles and Syntactic Hierarchiesmentioning
confidence: 99%